Psychosocial aspects of the school institution - Rubilar S., Luis (Revista de Psicología, 1997)
The dialectical relationship between the individual microstructure and the social macrostructure is mediated and channeled through specific social formations: institutions. Here the educational institutions are described, relieving psycho-social aspects of their structure and operation, especially those of a spatio-temporal, group and communicational nature. The analysis is contextualized in the current national environment and with the objective of a better understanding of the teacher-student relationship.